K(q)ueer-pop body: Strategi performativitas gender dari grup boyband Korea XLOV - Vallerine Firstya Angelica; Natasha Maitreyani Aditio; Martinus Danang Pamungkas (Metahumaniora, 2026)
This study attempts to analyze how Boygroup's gender performativity strategy works in the arena of hegemonic masculinity culture. XLOV, as a Boygroup that emerged in the current era of popular culture, has attempted to deconstruct the roles and identities of traditional masculinity norms towards a new form of performative masculinity. Using the concept of new masculinity combined with gender performativity theory, the researcher found that XLOV's gender performativity strategy is evident in their clothing styles, choreographed movements, and other symbolism that appears in their music videos. The implication of this research is that consumers of popular culture can educate themselves about gender roles and identities, which are increasingly fluid, especially amid the rapid growth of popular culture.